Systematic Review of Randomized Clinical Trials on Safety and Efficacy of Pharmacological and Nonpharmacological Treatments for Retinitis Pigmentosa - Marta Sacchetti; Flavio Mantelli; Daniela Merlo; Alessandro Lambiase (Journal of Ophthalmology)
Aims. Several treatments have been proposed to slow down progression of Retinitis pigmentosa (RP), a hereditary retinal degenerative condition leading to severe visual impairment. The aim of this study is to systematically review data from randomized clinical trials (RCTs) evaluating safety and efficacy of medical interventions for the treatment of RP. Methods. Randomized clinical trials on medical treatments for syndromic and nonsyndromic RP published up to December 2014 were included in the review. Visual acuity, visual field, electroretinogram, and adverse events were used as outcome measures. Results. The 19 RCTs included in this systematic review included trials on hyperbaric oxygen delivery, topical brimonidine tartrate, vitamins, docosahexaenoic acid, gangliosides, lutein, oral nilvadipine, ciliary neurotrophic factor, and valproic acid. All treatments proved safe but did not show significant benefit on visual function. Long term supplementation with vitamin A showed a significantly slower decline rate in electroretinogram amplitude. Conclusions. Although all medical treatments for RP appear safe, evidence emerging from RCTs is limited since they do not present comparable results suitable for quantitative statistical analysis. The limited number of RCTs, the poor clinical results, and the heterogeneity among studies negatively influence the strength of recommendations for the long term management of RP patients.